PENDIDIKAN KEAGAMAAN PADA KOMUNITAS MUSLIM INDONESIA DI HONG KONG - Rudy Harisyah Alam (Badan Litbang dan Diklat Kementerian Agama RI, 2016)
This writing is a result of research on Religious Education of Indonesia Moslem Community in Hong Kong,to find out which institutions and whatcharacteristics become providers of the religious education for Indonesian Moslem community in Hong Kong. This research uses explorativequalitative approach by data collection technique through a combination between individual and group interview technique, field observation, as well as document and literature study. The result of this study shows: firstly, almost a half of the Moslem community in Hong Kong is Indonesian Moslem community, they are generally come from migrant workers in non-formal sectors (such as maid) which in social, political and economicalaspect they have a weak bargaining position in their life in Hong Kong. Secondly, the Indonesian Moslem Community in Hong Kong generallyconsists of female workers and they are not allowed taking their children or family with them, their immediate needs are guidance and educational service on religion for their own needs in the form of a non-formal religion educational service. The need on education and religion are obtainedby establishing religious groups, associations or organizations which in general are not registered as an official organization in the Government of Hong Kong. Thirdly, they regularly strive to meet their needs on religious guidance and education by holding a routine group religious guidance heldSundays, as the day is holiday which in general is granted to the majority of Indonesian workers.tulisan ini merupakan hasil penelitian tentang Pendidikan Keagamaan pada Komunitas Muslim Indonsesia di Hong Kong, yang bertujuan untuk mengetahui institusi-institusi dan karakteristik apa yang menjadi penyedialayanan pendidikan keagamaan komunitas muslim Indonesia di Hongkong. Penelitian ini menggunakan pendekatan kualitatif-eksploratif dengan teknik pengumpulan data melalui mengombinasikan teknik wawancara individualdan kelompok, observasi lapangan, serta studi dokumen dan literatur. Hasil setudi ini ditemukan antara lain: pertama, hampir separuh dari komunitas muslim di Hong Kong adalah kaum muslim Indonesia, umumnya mereka berasal dari kalangan pekerja migran pada sektor non formal (pembantu rumah tangga) yang secara sosial, politik dan ekonomi tidak memiliki daya tawar yang kuat dalam kehidupan di negara Hong Kong. Kedua, Komunitas muslim Indonesia di Hong Kong umumnya adalah pekerja wanita dan tidak diperkenankan membawa anak atau keluarga, kebutuhan mendesak yang mereka hadapi adalah layanan bimbingan dan pendidikan agama bagi diriÂ mereka sendiri, berupa layanan pendidikan keagamaan non-formal. Kebutuhanpendidikan dan keagamaan diperoleh dengan cara membentuk kelompok, perkumpulan atau organisasi keagamaan yang umumnya tidak terdaftarÂ sebagai organisasi resmi pada pemerintah Hong Kong. Ketiga, secara regulermereka berupaya memenuhi kebutuhan akan bimbingan dan pendidikan keagamaan melalui pengajian rutin yang diadakan setiap hari minggu, sesuai waktu libur yang umumnya tersedia bagi mayoritas pekerja Indoensia.